The acquisition of private companies - W.J.L. Knight (Longman, 1992)
Dealing with the law, taxation and procedure of acquiring shares in private companies, this edition covers the Finance Act 1991 and the Companies Act 1989, together with a new chapter on structuring transactions and new material on environmental issues and European acquisitions